Synthesis, photophysics, photochemistry and fluorescence quenching studies on highly soluble substituted oxo-titanium(IV) phthalocyanine complexes - Erdogmus, Ali; Durmus, Mahmut; Ugur, Ahmet Lufti; Avciata, Oguzhan; Avciata, Ulvi; Nyokong, Tebello (ELSEVIER SCIENCE SA, 2010)
The synthesis, photophysical and photochemical properties of soluble 3,4-(methylendioxy)-phenoxy substituted oxo-titanium(IV) phthalocyanines (4-6) are reported for the first time. The new compounds have been characterized by elemental analysis, FT-IR, H-1 NMR spectroscopy, electronic spectroscopy and mass spectra. General trends are described for fluorescence lifetimes and fluorescence, photodegradation and singlet oxygen quantum yields, of these compounds in dimethylsulfoxide (DMSO) and toluene. The effects of the position of the substituents and solvent effect on the photophysical and photochemical parameters of the oxo-titanium(IV) phthalocyanines (4-6) are also reported. The fluorescence of the substituted oxo-titanium(IV) phthalocyanine complexes (4-6) is effectively quenched by 1,4-benzoquinone (BQ) in both DMSO and toluene. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Titanium; Fluorescence; Photochemistry; Photophysics; NONLINEAR-OPTICAL PROPERTIES; DERIVATIVES; PHOTOSENSITIZERS; BEHAVIOR; ALPHA; ABSORPTION; SEPARATION; ZINC(II); GALLIUM; LIQUID; Materials Science; Physics; Polymer Science